An integrated proteomic and transcriptomic signature of the failing right ventricle in monocrotaline induced pulmonary arterial hypertension in male rats - Hindmarch, Charles Colin Thomas; Tian, Lian; Xiong, Ping Yu; Potus, Francois; Bentley, Rachel Emily Teresa; Al-Qazazi, Ruaa; Prins, Kurt W.; Archer, Stephen L. (Frontiers in Physiology, 2022)
Aim: Pulmonary arterial hypertension (PAH) is an obstructive pulmonary vasculopathy that results in death from right ventricular failure (RVF). There is limited understanding of the molecular mechanisms of RVF in PAH. Methods: In a PAH-RVF model induced by injection of adult male rats with monocrotaline (MCT; 60mg/kg), we performed mass spectrometry to identify proteins that change in the RV as a consequence of PAH induced RVF. Bioinformatic analysis was used to integrate our previously published RNA sequencing data from an independent cohort of PAH rats. Results: We identified 1,277 differentially regulated proteins in the RV of MCT rats compared to controls. Integration of MCT RV transcriptome and proteome data sets identified 410 targets that are concordantly regulated at the mRNA and protein levels. Functional analysis of these data revealed enriched functions, including mitochondrial metabolism, cellular respiration, and purine metabolism. We also prioritized 15 highly enriched protein:transcript pairs and confirmed their biological plausibility as contributors to RVF. We demonstrated an overlap of these differentially expressed pairs with data published by independent investigators using multiple PAH models, including the male SU5416-hypoxia model and several male rat strains. Conclusion: Multiomic integration provides a novel view of the molecular phenotype of RV failure in PAH which includes dysregulation of pathways involving purine metabolism, mitochondrial function, inflammation, and fibrosis.